USE YOUR HEAD TO MAKE LEARNING BY HEART EASY, CZYLI O IDIOMACH Z PUNKTU WIDZENIA LINGWISTYKI KOGNITYWNEJ - Szudy-Sojak, Aleksandra (Neofilolog, 2019)
The aim of the article is to focus on the cognitive mechanisms that motivate the meanings of idioms as presented by Zoltán Kövesces. Contrary to traditional view, according to which an idiom is an expression whose overall meaning differs from the meanings of its constituents, cognitive linguistics claims that the meaning of a large number of idioms is not arbitrary but motivated. It rejects the “dead metaphor” perspective in favour of underlining relations between domains. The approach, which underlines the embodied aspects of language and cognition, appears tempting in particular in relation to body-related idioms. Metaphorical awareness can play a role of comprehensible input in learning idiomatic language.